2019
DOI: 10.1007/s00432-019-02881-8
|View full text |Cite|
|
Sign up to set email alerts
|

Neoadjuvant chemoradiotherapy delivered with helical tomotherapy under daily image guidance for rectal cancer patients: efficacy and safety in a large, multi-institutional series

Abstract: Purpose Helical tomotherapy (HT) has been recently introduced in the neoadjuvant treatment of locally advanced rectal cancer. Aim of this study is to report the toxicity and local control rates of a large series of locally advanced rectal cancer patients treated with neoadjuvant chemotherapy and HT under daily image guidance followed by surgery. Methods Data from 117 locally advanced rectal cancer patients treated at two Swiss Radiotherapy departments were collected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(47 reference statements)
0
3
0
1
Order By: Relevance
“…155 Point: IMRT improves clinical endpoints Multiple retrospective studies have shown that preoperative IMRT or volumetric-modulated arc therapy (VMAT, arc-based IMRT) is associated with a clinically significant reduction in GI or genitourinary (GU) toxicity, with or without improvement in LC compared with 3D-CRT. 106,107,[170][171][172] Furthermore, these modalities can potentially prevent delays in time to surgery and reduce hospitalizations, emergency department visits, and treatment breaks. 173 However, no significant differences were noted in tumor responses, DFS and OS.…”
Section: The Era Of Imrtmentioning
confidence: 99%
“…155 Point: IMRT improves clinical endpoints Multiple retrospective studies have shown that preoperative IMRT or volumetric-modulated arc therapy (VMAT, arc-based IMRT) is associated with a clinically significant reduction in GI or genitourinary (GU) toxicity, with or without improvement in LC compared with 3D-CRT. 106,107,[170][171][172] Furthermore, these modalities can potentially prevent delays in time to surgery and reduce hospitalizations, emergency department visits, and treatment breaks. 173 However, no significant differences were noted in tumor responses, DFS and OS.…”
Section: The Era Of Imrtmentioning
confidence: 99%
“…Os pesquisadores mostraram que a quimiradioterapia administrada com a TH sob orientação diária da imagem é segura, com baixas taxas de toxicidade aguda e tardia. Foi proposto que técnicas altamente conformes, sob orientação diária da imagem, possam ser o padrão de tratamento no tratamento neoadjuvante de pacientes com câncer retal localmente avançado (De Bari et al, 2019). Os trabalhos apresentados por de Yang et al, (2019), Yu et al, (2018) e Araujo-Mino et al, (2018) avaliaram a utilização da quimioterapia e radioterapia em relação a segurança e eficácia, além da toxicidade.…”
Section: Metodologiaunclassified
“…The number of patients in the cohort was not reported at 5 years and only 11 remained at 10 years, therefore the 2 year time-point was used. Two studies reported no GU complications (117 and 69 patients respectively 36,37 ) so contributed no information to the meta-analysis.…”
Section: Genitourinary (N = 13)mentioning
confidence: 99%